2018
DOI: 10.1016/j.jacc.2018.07.071
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Landscape of Diabetes Therapy for Cardiovascular Risk Reduction

Abstract: Type 2 diabetes mellitus (T2D) is a major risk factor for cardiovascular disease (CVD), the most common cause of death in T2D. Despite improved risk factor control, however, adults with T2D continue to experience substantial excess CVD risk. Until recently, however, improved glycemic control has not been associated with robust macrovascular benefit. The advent of two new classes of anti-hyperglycemic agents, the sodium-glucose cotransporter-2 inhibitors (SGLT2-i) and the glucagon-like peptide-1 receptor agonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 87 publications
0
36
1
2
Order By: Relevance
“…Meanwhile, the mechanisms by which the two drug classes exert cardiac protective effects are summarized in two recent review articles [ 24 , 25 ]. Among all mechanisms mentioned in the two articles [ 24 , 25 ], an important mechanism is that the two drug classes are able to reduce cardiac afterload [ 26 , 27 ] and preload [ 28 30 ] by various means.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the mechanisms by which the two drug classes exert cardiac protective effects are summarized in two recent review articles [ 24 , 25 ]. Among all mechanisms mentioned in the two articles [ 24 , 25 ], an important mechanism is that the two drug classes are able to reduce cardiac afterload [ 26 , 27 ] and preload [ 28 30 ] by various means.…”
Section: Discussionmentioning
confidence: 99%
“…29 Increasingly, as novel diabetes drugs continue to improve cardiovascular outcomes, we expect the positive reductions in CVD mortality among individuals with diabetes to continue. 30 DM is a multisystem disease and, as DM-related vascular complications continue to decline, a rise in other causes of death is expected. For example, we found that those with DM on their death record as three times as likely to have hypertension and renal disease co-reported on their death records.…”
Section: Discussionmentioning
confidence: 99%
“…Although overall control of major CV risk factors has greatly improved over the last 10 years, 34,35 the rates of CV events are still higher in adults with T2D than in the non‐diabetic population 36 . Up to now, enforcing tight glycaemic control has failed to convincingly show a clear benefit on macrovascular complications, 34 whereas the benefits of optimal glucose control on microvascular outcomes have been shown in several large trials 28,37–39 …”
Section: The Changing Scenariomentioning
confidence: 99%